Standing to View Other People’s Land: The D.C. Circuit’s Divided Decision in Sierra Club v. Jewell - Mank, Bradford C. (Columbia Journal of Environmental Law, 2019)
In its divided 2014 decision in Sierra Club v. Jewell, the U.S. Court of Appeals for the District of Columbia Circuit held that plaintiffs who observe landscape have Article III standing to sue in federal court to protect those views even if they have no legal right to physically enter the private property that they view. Two earlier decisions had reached similar conclusions, but have had little impact. The D.C. Circuit’s decision could significantly enlarge the ability for plaintiffs to sue federal agencies or private parties over changes to private lands that the plaintiffs have no right to enter. Because the Supreme Court has inconsistently applied both strict and liberal approaches to standing, it is difficult to predict how it would decide this issue. If it addresses whether plaintiffs must have a legal interest in any property they seek standing to protect, the Supreme Court might be forced to resolve the contradictions in its standing doctrine. Part II explains the basic principles of constitutional Article III standing. Part III addresses the district court’s initial decision rejecting standing and the divided D.C. Circuit decision finding standing in Sierra Club v. Jewell. Part IV examines two prior decisions concluding that observers have standing to challenge changes to property they do not own or have a right to enter. Part V discusses how the Supreme Court might address the issue of standing rights for those who view private lands they have no right to enter.